Are the urban poor always worse off ? Socioeconomic differentials in adult cause specific mortality at the periphery of Ouagadougou, Burkina Faso - (:unkn) unknown (My University, 2014)
In the cities of less developed countries, while poorer residents are likely to be at greater risk of dying from communicable diseases and injuries, wealthier residents may suffer from a greater burden of non-communicable diseases. It remains thus unclear whether poorer African adult city dwellers are in worse health than their better-off counterparts. In this paper, we describe the social inequalities that characterize adult mortality (individuals aged 15 to 59) at the periphery of Ouagadougou, the capital city of Burkina Faso. Using data from the Ouagadougou Health and Demographic Surveillance System from 2009 to 2011, we test whether factors such as levels of education, poverty and informal settlement are related to risks of premature deaths among adults. We conduct this analysis for all-cause mortality, and also considered three main categories of causes of death: communicable diseases, non-communicable diseases and external causes. Restricting the analysis to adults born in Ouagadougou, we found that the urban poor face a considerable health penalty compared to the less poor, which is consistent with expectation based on existing literature. Wealthier non-migrants face relatively lower risks of premature death, from both communicable and non-communicable diseases. Adult migrants exhibit very different patterns of mortality, which distort the overall picture of health inequalities in the city. Wealthier adult migrants and migrants living in formal settlements face a greater risk of dying from non-communicable diseases. These particular patterns are probably due to selective in and/or out-migration, and maybe to greater levels of exposure to non-communicable diseases by migrants. These results call for more attention to the effects of migration when studying rural-urban and social differentials of health in Sub-Saharan Africa.
Keywords: African Research